Peran Kyai Dalam Pengaruh Moderasi Beragama di Tengah Isu Digital - Nur Fauzi, Ahmad; Nur Fadhila, Indah; Yaenuri, Ali (Kartika: Jurnal Studi Keislaman, 2025)
This research originates from the researcher’s concern about the state of religious moderation in the digital space, despite the Ministry of Religious Affairs of the Republic of Indonesia having emphasized the discourse on religious moderation since 2019. However, the actualization of this discourse has not been fully realized, especially on social media. The research examines this shortcoming by exploring the role of "Social Media Kyai (Medsos)" in creating counter-narratives against extremist Islamic groups in the digital space. The goal of this research is to map the extent of the contestation of religious moderation and to analyze the contribution of "Kyai Medsos" in addressing the issue of religious moderation in the digital space. The methodology used in this study is library research, with the collected data analyzed through a content analysis approach. The findings are: 1) The contestation between "Kyai Medsos" and extremist Islamic groups is reflected in debates over the relationship between Islam and the State. 2) The contribution of "Kyai Medsos" in addressing the issue of religious moderation in the digital space is by mainstreaming moderate (positive) content in the digital space. The conclusion of this research suggests that netizens need to understand and filter information from social media to ensure that religious moderation in the digital space is genuinely maintained.